'Discursive news values analysis' of Iranian crime news reports: Perspectives from the culture. Issue 4 (August 2019) - Makki, Mohammad
This article is concerned with 'how' newsworthiness is constructed linguistically/discursively in a sample of Iranian crime and misbehaviour reports. This is new as both linguistic analysis of 'crime reports' and the context of 'Iranian journalism' are among under-researched areas. One-month worth editions of two Iranian/Farsi language newspapers were collected, and the data were analysed both quantitatively and qualitatively with reference to the analytical framework of Bednarek and Caple. While the quantitative analysis showed the construction of Eliteness as the most frequent news value in both newspapers, there were differences in the construction of news values between the newspapers. Qualitative analysis of the data also showed the construction of news values in line with the sociocultural values prevalent in the society as well as the possible role of state and political authorities.